An analysis of English national final examination for junior high school in terms of validity and reliability - Aris Sugianto (Journal on English as a Foreign Language, 2016)
The purpose of this study is to analyze the English National Final Examination for Junior High School. Validity and reliability are the two kinds of characteristics of a good test which are concerned. Since the five packages of the test are the same in content and only different on the placement of the items, so it is considered to take only one package becomes sample. This study was analyzed by using the descriptive method. Content validity was analyzed by comparing the materials in the syllabus to the items of the test, and construct validity was analyzed by comparing the indicators in the syllabus to the items of the test. While the reliability was analyzed by using Kuder-Richardson Formula (KR20). The result of the study shows that the English National Final Examination for Junior High School was valid and reliable. The content validity shows 100% valid, and the construct validity shows 100% valid. While the reliability shows coefficient 0.89, and it is reliable. So, the English National Final Examination for Junior High School has fulfilled the characteristics of a good test.